2010
DOI: 10.4161/oxim.3.2.11157
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dietary Supplement Containing Multiple Phytochemicals and Vitamins Elevates Hepatorenal and Cardiac Antioxidant Enzymes in the Absence of Significant Serum Chemistry and Genomic Changes

Abstract: A novel dietary supplement composed of three well-known phytochemicals, namely, Salvia officinalis (sage) extract, Camellia sinensis (oolong tea) extract, and Paullinia cupana (guarana) extract, and two prominent vitamins (thiamine and niacin) was designed to provide nutritional support by enhancing metabolism and maintaining healthy weight and energy. The present study evaluated the safety of this dietary supplement (STG; S, sage; T, tea; G, guarana) and assessed changes in target organ antioxidant enzymes (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…The anti-inflammatory and anti-anxiety properties of Salvia officinalis , including thiamin, rosmarinic acid, carnosic acid, gallic acid, flavonoids, diterpenes and phenolic acids, as well as the phytoestrogenic contents of the plant seemed to be involved in reducing the mental symptoms of the sufferers. It is also suggested that neurochemical receptors in the CNS may play a key role in these effects [22,25,26]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anti-inflammatory and anti-anxiety properties of Salvia officinalis , including thiamin, rosmarinic acid, carnosic acid, gallic acid, flavonoids, diterpenes and phenolic acids, as well as the phytoestrogenic contents of the plant seemed to be involved in reducing the mental symptoms of the sufferers. It is also suggested that neurochemical receptors in the CNS may play a key role in these effects [22,25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…The exact etiology for a reduction of the physical symptoms of PMS is not yet well understood, but it seems that anti-prostaglandins play a critical role as mediating factor. Anti-inflammatory and antioxidant properties of Salvia officinalis due to the contents of rosmarinic acid, carnosic acid, and caffeic acid [22,25,26] and the anti-prostaglandin effects of carnosol and carnosic acid [26] in this plant could help reduce the PMS-associated physical as well as psychological symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guaraná seed extract exhibits a powerful antioxidant activity, and in combination with vitamins and minerals, it improves cognitive task performance and attenuates increased mental fatigue associated with extended cognitive task performance (Bulku et al, 2010;Kennedy et al, 2008). Guaraná seed products are increasingly being used as a weight loss product in the form of powder, tablets and jams (Basile et al, 2005;Henman, 1982;Seidemann, 1998), and it is widely consumed by athletes who believe that it presents ergogenic and "fat burning" effects (Lima et al, 2005).…”
Section: Use Of P Cupana In Food Drinks and Dietary Supplementsmentioning
confidence: 99%
“…Kennedy et al (2008) concluded that multivitamin-mineral food supplements fortified with Guaraná can improve cognitive performance and reduce the mental fatigue with sustained mental effort. Another dietary supplement, which is composed of three well-known phytochemicals, namely, Salvia officinalis L. (sage) extract, Camellia sinensis (L.) Kuntze (oolong tea) extract, and P. cupana (Guaraná) extract, and two prominent vitamins (thiamine and niacin), was designed to provide nutritional support by enhancing metabolism and maintaining healthy weight and energy (Bulku et al, 2010). The mixed herbal preparation "YGD," which contains Yerbe Maté (leaves of Ilex paraguayensis Hook), Guaraná (seeds of P. cupana) and Damiana (leaves of Turnera diffusa Willd.…”
Section: Use Of P Cupana In Food Drinks and Dietary Supplementsmentioning
confidence: 99%